Dekonstruksi Filosofi Pendidikan Pesantren Salafiyah: Studi Analisis Konsep Sanad Keilmuan Pesantren Al-Haqiqi Sidosermo Surabaya - Muhtar, Mohamad Khusnial; Novita, Almi (Aqlania, 2023)
Scholarly sanad is one of the concepts in the philosophy of education of pesantren salafiyah centrally and fundamentally. This research attempts to deconstructively examine this concept from the perspective of Pesantren Al-Haqiqi Sidosermo Surabaya, identified as pesantren salafiyah. It employs a qualitative method with a philosophical approach. Data were collected through interviews and participatory observation, involving caregivers, teachers, and students from the pesantren. The data was analyzed using Derrida’s deconstruction theory. The results reveal that the Pesantren Al-Haqiqi emphasizes the urgency of scholarly sanad in the teaching-learning process, believing it preserves the purity of Islamic teachings from Prophet Muhammad, ensures continuity of knowledge with the Prophet, and brings blessings. However, considering the human dimension in education, which includes subjective and contextual factors, this raises ambiguities and oddities in its meaning and assumptions. The same applies to the guarantee of knowledge continuity and blessings. Recognition of the plurality of knowledge sources, critical examination of traditional authorities, and the development of contextual and innovative skills emerge as reconstructive responses to these ambiguities and oddities. This strengthens the assumption that Islam is a doctrine for all times and places that has momentarily been shaken.